Student - Volunteer: Aspect of Self-Realization Value in the Context of the Covid-19 Pandemic - Tavstukha, Olga G.; Shagieva, Rosalina V.; Allagulov, Artur M.; Ayakoz, Yakub A.; Kurbanov, Rashad A.; Belyalova, Asiya M.; Tararina, Larisa I. (Cuestiones Políticas, 2020)
In the context of the COVID-19 pandemic, the issues of social capital and mutual aid networks become particularly relevant for the student volunteer in Russia, who independently and, at their own discretion, provides assistance, support and mutual aid. To people in need, as a vital incentive for self-realization. This research aimed to identify the motivating aspects of the need for self-realization of a student volunteer in practical activities to overcome COVID-19. The study method was the test, which allows to identify the characteristics of the content of the value aspects of the self-realization of the volunteer student, determined by the global context of crisis. By way of conclusion, the characteristics of the coronavirus pandemic are revealed as an extraordinary condition for the activity of a student volunteer. Based on the results of the study, a self-realization value model of a volunteer student is confirmed in the extraordinary conditions of the coronavirus pandemic. The practical importance of the model is demonstrated with the help of cognitive criteria typical of activity-based social psychology for the formation of value aspects of the self-realization of a volunteer student.